S192. EFFECTS OF NICOTINE INTAKE ON NEUROPLASTICITY IN SMOKING AND NON-SMOKING PATIENTS WITH SCHIZOPHRENIA. (18th May 2020) - Pross, Benjamin; Schulz, Patrick; Güler, Duygu; Papazova, Irina; Wagner, Elias; Maurus, Isabel; Löhrs, Lisa; Strube, Wolfgang; Padberg, Frank; Falkai, Peter; Hasan, Alkomiet
Abstract: Background: Cortical plasticity – the ability to reorganize synaptic connections and adapt to environmental changes – appears to be impaired in schizophrenia patients. Results suggest the dysfunctional plasticity to be a key pathophysiological mechanism. Different non-invasive brain stimulation (NIBS) techniques have been used to modulate and induce cortical plasticity. In healthy subjects, nicotine was shown to play an important role in plasticity induction and is capable to alter cortical excitability and plasticity, induced by NIBS techniques. Our goal was to investigate the promising effects of a nicotine receptor activation done by Varenicline and the combination with anodal transcranial direct current stimulation (a-tDCS) on neuroplastic changes in schizophrenia patients. Methods: Our sample consisted out of twenty-four individuals with schizophrenia, twelve smokers and twelve non-smokers. Every participant received Varenicline and Placebo, combined with anodal transcranial direct current stimulation (a-tDCS), to induce non-focal plasticity. We inferred plasticity changes by monitoring changes in cortical excitability. This was done via motor-evoked potentials (MEPs) elicited by transcranial magnetic stimulation (TMS). The MEPs were recorded before and three hours after Varenicline/Placebo intake. Following the direct current stimulation, we monitored excitability changes for up to one hour. Results: Significant effects through the mere Varenicline consumption or withdrawal effects could not be found in any group. However, we observed a numeric temporary decrease of excitability after a-tDCS in non-smokers following Varenicline intake. This decrease compared to the placebo condition was visible 20 minutes after a-tDCS but vanished over time. Smokers did not show any excitability changes after a-tDCS and the nicotinic receptor stimulation did not show any influence. Excitability changes after stimulation in contrast to the baseline measurement were not evident. Discussion: Our results show that an activation of nicotinic receptors in schizophrenia patients does not induce excitability changes. The modulating effect of nicotine in plasticity induction via anodal transcranial direct current stimulation could not be confirmed for patients with schizophrenia. We could show that chronic nicotine consumption in patients with schizophrenia or nicotine withdrawal does not lead to fundamental excitability changes. Acute nicotine consumption has only small effects on cortical excitability in non-smokers.